An adaptive observer design approach for a class of discrete-time nonlinear systems - Srinivasarengan, Krishnan; Ragot, José; Aubrun, Christophe; Maquin, Didier (Zielona Góra: Uniwersytet Zielonogórski)
We consider the problem of joint estimation of states and some constant parameters for a class of nonlinear discrete-time systems. This class contains systems that could be transformed into a quasi-LPV (linear parameter varying) polytopic model in the Takagi-Sugeno (T-S) form. Such systems could have unmeasured premise variables, a case usually overlooked in the observer design literature. We assert that, for such systems in discrete-time, the current literature lacks design strategies for joint state and parameter estimation. To this end, we adapt the existing literature on continuous-time linear systems for joint state and time-varying parameter estimation.
Keywords: adaptive observer; joint state and parameter estimation; Takagi-Sugeno model; time-varying parameter estimation; sector nonlinearity transformation; discrete-time nonlinear systems